2013
DOI: 10.1186/1471-2164-14-17
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of microsatellite markers for Brachiaria ruziziensisobtained by partial genome assembly of Illumina single-end reads

Abstract: BackgroundBrachiaria ruziziensis is one of the most important forage species planted in the tropics. The application of genomic tools to aid the selection of superior genotypes can provide support to B. ruziziensis breeding programs. However, there is a complete lack of information about the B. ruziziensis genome. Also, the availability of genomic tools, such as molecular markers, to support B. ruziziensis breeding programs is rather limited. Recently, next-generation sequencing technologies have been applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 22 publications
10
47
2
2
Order By: Relevance
“…The PIC value in this study is within the range reported by Silva et al [14], Jungmann et al [15], and Vigan et al [16], but was lower than that found by Jungmann et al [17] and Pessoa-Filho et al [18]. Similarly, the average numbers of allele detected per loci (5.45) was in the range reported by Silva et al [14], Jungmann et al [15], and Vigan et al [16], but was about half and one-third of that reported by Jungmann et al [17] and Pessoa-Filho et al [18], respectively. However, these comparisons between studies may not be conclusive due to differences in types and number of germplasms and markers used among studies.…”
Section: Discussionsupporting
confidence: 91%
“…The PIC value in this study is within the range reported by Silva et al [14], Jungmann et al [15], and Vigan et al [16], but was lower than that found by Jungmann et al [17] and Pessoa-Filho et al [18]. Similarly, the average numbers of allele detected per loci (5.45) was in the range reported by Silva et al [14], Jungmann et al [15], and Vigan et al [16], but was about half and one-third of that reported by Jungmann et al [17] and Pessoa-Filho et al [18], respectively. However, these comparisons between studies may not be conclusive due to differences in types and number of germplasms and markers used among studies.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency, type and distribution of the 4,489 potential SSRs were also analyzed in the present study. Among the 4,489 SSRs, trinucleotide repeat motifs were the most abundant (3,868, 86.2 %) (Table 5), which is similar to the P. maximum transcriptome (86 %) [34] and the Brachiaria ruziziensis genome (85.2 %) [87], followed by dinucleotide (363, 8.09 %), tetranucleotide (173, 3.85 %), pentanucleotide (54, 1.20 %) and hexanucleotide (31, 0.69 %) repeat motifs. The total distribution of SSR motifs was similar to that determined for P. maximum [34], whereas in B. ruziziensis [87], tetranucleotide motifs were more abundant than dinucleotide motifs (Additional file 10).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the steady decrease in cost per sequenced nucleotide and increase in throughput data, NGS technologies have become a powerful approach for the high-throughput discovery of genes; they generate a large amount of sequence data for molecular marker identification (Iorizzo et al, 2011;Silva et al, 2013). Recently, de novo transcriptome assembly using Illumina sequences has been successfully developed and widely applied in various important plant species including rice, wheat, and maize (Lu and Lu.…”
Section: Discussionmentioning
confidence: 99%